World watch geography Skills book 1 A geography skills book for grade 6 - Moorcroft, Christine; Moorcroft, Christine (Karachi Oxford University Press, 2024)
It builds on students' experience from earlier work in geography by introducing higher-level geographical skills. It presents a student-friendly approach with a conversational tone to engage their interest. It's aim to foster students' geographic literacy, spatial awareness, critical thinking, and practical application of geographical concepts to enhance their overall understanding of the world and their place within it.
Keywords: Geography skill book